Theoretical foundations and new approaches to preventive conservation in built heritage: From Ruskin to sustainable conservation - Estrada Castillo, Alicia (2026)
The postulates of conservation-restoration theorists, international charters and conventions constitute the guidelines for conservation work, which, together with the experiences in the protection of built heritage at least in the last fifty years, have generated debates on the suitability of treatments, giving rise to discourses consistent with sustainability. The present qualitative-documentary research shows that preventive conservation is a level of conservation in gradual theorization. Its minimum intervention criterion is respectful of the materiality and importance of cultural assets. Its peripheral strategies such as systematic maintenance help reduce the risk of deterioration, avoid the waste of resources and value traditional construction knowledge. The identification of its theoretical and deontological foundations was key to differentiating it from direct conservation and contributing to the understanding and consolidation of the new approach to sustainability in built heritage.